2000
DOI: 10.1097/00005344-200008000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with Inhaled Nitric Oxide and Intravenous Dobutamine During Pulmonary Hypertension in the Rabbit

Abstract: Combination therapy with an intravenous inovasodilator and inhaled nitric oxide (NO) may be appropriate in patients with pulmonary hypertension and associated right ventricular failure. We examined whether dobutamine and inhaled NO would have additive pulmonary vasodilator effects in experimental pulmonary hypertension. Pulmonary hypertension was produced in anesthetized, mechanically ventilated rabbits by infusion of U46619, a thromboxane analogue. Dobutamine was administered in increasing doses (2.5-20 micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…It has previously been reported that the effects of dobutamine are highly dose-and flow dependent (5,42). As a consequence, the effects of this dose of dobutamine are likely different in CTL and HPH conditions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It has previously been reported that the effects of dobutamine are highly dose-and flow dependent (5,42). As a consequence, the effects of this dose of dobutamine are likely different in CTL and HPH conditions.…”
Section: Discussionmentioning
confidence: 98%
“…The dosage regimen of 5 g·kg Ϫ1 ·min Ϫ1 was chosen because it is within the dosage range (2.5-10 g·kg Ϫ1 ·min Ϫ1 ) most commonly used in experimental (5,52) and clinical pulmonary hypertension (34). In CTL mice, dobutamine caused a significant decoupling through an increase in contractility and larger increase in effective arterial elastance.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary Vascular Pressure/Flow Relationships. Dobutamine has been reported to decrease PVR in experimental (1,5) and clinical (4, 6) pulmonary hypertension. Accordingly, dobutamine is believed to act as a pulmonary vasodilator and has been used as such, for example, to evaluate the reversibility of pulmonary hypertension in patients with advanced left heart failure considered for cardiac transplantation (6).…”
Section: Discussionmentioning
confidence: 99%
“…All these disease states are complicated by variable degrees of pulmonary hypertension (1)(2)(3)(4). At doses usually given in clinical practice (up to 20 g·kg Ϫ1 ·min Ϫ1 ), dobutamine has been reported to decrease pulmonary vascular resistance (PVR), in experimental (1,5) and clinical (4, 6) pulmonary hypertension. However, whether dobutamine decreases PVR independently of associated changes in flow remains uncertain.…”
mentioning
confidence: 99%
“…Dobutamine is an inotrope that acts primarily through ␤ 1 -adrenergic receptors to augment myocardial contractility and reduce left ventricular afterload (54). In animal models of acute pulmonary hypertension, dobutamine in doses up to 5 g/kg per min significantly decreased PVR while slightly increasing cardiac output (55,56). However, at doses of 5-10 g/kg per min, dobutamine caused significant tachycardia without improving pulmonary vascular resistance.…”
Section: Pharmacologic Therapy Of Pulmonary Hypertensionmentioning
confidence: 99%